ANALISA PELAPORAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) BERDASARKAN PEDOMAN GLOBAL REPORTING INITIATIVES (GRI) - FEBRINA WAHYU SAFITRI, NANDA Febrina Wahyu (Jurnal Akuntansi AKUNESA, 2013)
The chemical and industrial companies can potential raise to environmental issues. This research discusses CSR reporting with guide of the GRI G3.1 in the chemical and industrial companies. The data resources used secondary data from annual reports and sustainability report for the chemical and industrial companies in Indonesia which is obtained through sources from the Indonesia Stock Exchange (IDX) as well as the official website of the respective companies.The conclusion found that the disclosure of CSR reporting in chemical and industrial companies is still relatively weak and the most indicator has disclosure are economic and social . It can be seen from a total of 45 companies, only two companies reported CSR in the sustainability report. While CSR disclosure in annual reports is also still relatively low. Average disclosure is still below 50% of the GRI standard. Keywords: GRI, Sustainability report, Corporate Social Responsibility